Standalone and Minigrid-Connected Solar Energy Systems for Rural Application in Rwanda: An In Situ Study. (5th October 2021) - Chang, Kuo-Chi; Hagumimana, Noel; Zheng, Jishi; Asemota, Godwin Norense Osarumwense; Niyonteze, Jean De Dieu; Nsengiyumva, Walter; Nduwamungu, Aphrodis; Bimenyimana, Samuel
Abstract : In recent years, several factors such as environmental pollution, declining fossil fuel supplies, and product price volatility have led to most countries investing in renewable energy sources. In particular, the development of photovoltaic (PV) microgrids, which can be standalone, off-grid connected or grid-connected, is seen as one of the most viable solutions that could help developing countries such as Rwanda to minimize problems related to energy shortage. The country's current electrification rate is estimated to be 59.7%, and hydropower remains Rwanda's primary source of energy (with over 43.8% of its total energy supplies) despite advances in solar technology. In order to provide affordable electricity to low-income households, the government of Rwanda has pledged to achieve 48% of its overal electrification goals from off-grid solar systems by 2024. In this paper, we develop a cost-effective power generation model for a solar PV system to power households in rural areas in Rwanda at a reduced cost. A performance comparison between a single household and a microgrid PV system is conducted by developing efficient and low-cost off-grid PV systems. The battery model for these two systems is 1.6 kWh daily load with 0.30 kW peak load for a single household and 193.05 kWh/day with 20.64 kW peak load for an off-grid PV microgrid. The hybrid optimization model for electric renewable (HOMER) software is used to determine the system size and its life cycle cost including the levelized cost of energy (LCOE) and net present cost (NPC) for each of these power generation models. The analysis shows that the optimal system's NPC, LCOE, electricity production, and operating cost are estimated to 1, 166, 898.0 USD, 1.28 (USD/kWh), 221, and 715.0 (kWh per year, 37, 965.91 (USD per year), respectively, for microgrid and 9284.4(USD), 1.23 (USD/kWh), and 2426.0 (kWh per year, 428.08 (USD per year), respectively, for a single household (standalone). The LCOE of a standalone PV system of an independent household was found to be cost-effective compared with a microgrid PV system that supplies electricity to a rural community in Rwanda.